INFLUENCE OF NOZZLE TYPE AND SPRAY RATES ON CORN AND WEED PLANTS DROP DEPOSITIONS - Terra, Marcelo Alves; Martins, Dagoberto [UNESP]; Costa, Neumarcio Vilanova da; Marchi, Sidnei Roberto de (Univ Federal Uberlandia, 2014)
The objective of this study was to evaluate different nozzles and spray rates on drop deposition in corn (Zea mays), Euphorbia heterophylla and Brachiaria plantaginea, both weeds located at and between crop rows. The experimental design established was complete random blocks with treatments arranged at 2 x 2 factorial scheme (2 nozzles types: DG11002VS flat flan and medium droplets, TXVK08 cone and very fine droplets; and 2 rates: 100 and 200 L ha(-1)) with four replications. The spray applications occurred at 13 days after corn germination (3-5 expanded leaves), when E. heterophylla and B. plantaginea plants had 2-4 and 2-3 leaves, respectively. Solution of Brilliant Blue (FD&C-1) dye at 3,000 ppm was used as spray tracer. It was concluded that the greatest average deposits in corn plants was provided by TXVK08, independently of the spray rates used. The most uniform deposits occurred when the spray rates of 200 L ha(-1) was used. Spray deposits were most uniform in B. plantaginea compared to E. heterophylla when both weds were located at crop row, independently of nozzle or spray rates. However, the DG 11002VS spray nozzle provided the most uniform drop deposition on B. plantaginea located between the rows, while the most efficient deposition over E. heterophylla located between rows was TXVK08.
Keywords: Spray technology; Zea mays; Euphorbia heterophylla; Brachiaria plantaginea